Embryo and foetus as seen by Orthodox Church - Koios, Nikolaos (Array, 2009)
The presentation of the opinion of the Orthodox Church about the value of the moral status of the embryo is based on the official statements of the local orthodox churches. Official statements about bioethical issues have been already released by the Orthodox Churches of Russia, Greece and Romania. The official Church texts express the orthodox anthropology which is based on the christological doctrine which consists of all the events of divine economy, such as the Annunciation of the Theotokos (divine conception) and the birth of the Virgin Mary and the Nativity of Jesus Christ, which lead to significant anthropological conclusions.From this standpoints emerge for the Orthodox Church about the embryo some of its inalienable rights: 1. the right to human identity, 2. the right to life, 3. the right to eternity. From all this forementioned perspective considers the Orthodox Church all the bioethical problems which have to do with the embryo